CURAHAN WAKTU WANITA TANI DAN KONTRIBUSINYA TERHADAP PENDAPATAN KELUARGA DI DESA JAKE KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI (STUDI KASUS BURUH TANI PERKEBUNAN KARET) - Ningtiyas, Elisabeth Pipit Putri Edi; Yulida, Roza; ', Rosnita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purposes of this research are to analysis outpouring time of women farm workers in family and factor-factor that affect to working hours. Analysis contribution income of women farm workers toward family’s income. The research used a survey method with sampling technique is purposive sampling. The sample of this research are 37 samples. Analysis of the data using ORDINARY LIEST SQUARE (OLS). The results showed that the average working hours of women farm workers in economic activity is 4,94 HKP/day, with the persentage is 53,00%, and in non economic activity is 4,38 HKP/day, with persentage is 47,00%. The dominant factors that affect working hours is amount of children. Contribution income of woman farm workers in rubber plantation toward family’s income is 33,8%. Keywords: Rubber Plantation, outpouring of time, Family’s Income